TEACHING EXTENSIVE LISTENING IN EFL CLASSROOM USING WEBSITE WWW.ER-CENTRAL.COM - Rohim, Abdul; Fitariana, Cut (Universitas Muhammadiyah Palembang, 2022)
The COVID 19 pandemic has affected living systems around the world; one of them is in the education system. It has led to the complete closure of schools, universities and colleges around the world. In response to this situation, many schools, universities and colleges are encouraged to use distance learning programs and open education applications and platforms in which schools and teachers can use these platforms to reach students remotely and limit educational interruptions. In this research, the website (www.er-central.com) was used as one of the distance learning programs for extensive listening by EFL students. This research aims to determine whether there is an effect of websites used by English language learners on the global spread of the COVID 19 pandemic. In this research, the reserchers used quantitative research in pre-experimental method design using one group of pre-tests and post-tests.. In pre-experimental research design, the researcher used concept one group Pre-test and Post-test for the third semester in university. The result of the data analysis indicated that there was significant difference of student’ test before and after being taught by using website. It can be said that there is a significant difference of student’s score after the treatment. It means that the website used is effective and can be used as a distance learning program for extensive listening in pandemic situations.